Pyridyl based ruthenium(II) catalyst precursors and their dihydride analogues as the catalytically active species for the transfer hydrogenation of ketones. (1st November 2018) - Zacharopoulos, Nikolaos; Kolovou, Evgenia; Peppas, Anastasios; Koukoulakis, Konstantinos; Bakeas, Evangelos; Schnakenburg, Gregor; Philippopoulos, Athanassios I.
Graphical abstract: The catalytic activity of a series of ruthenium(II) complexes of the type cis -[RuCl2 (PPh3 )2 (L)] (L = pyridyl based bifunctional ligand) for the transfer hydrogenation of various aromatic ketones using 2-propanol as the hydrogen source, is described. Isolated and spectroscopically characterized ruthenium(II)dihydride complexes have been proposed as the catalytically active species. Abstract: In this study we describe the one-pot and high yield synthesis of the ruthenium(II) complex cis -dichloride [RuCl2 (PPh3 )2 (L1)] (L1 = 4-methyl-2-(2′-pyridyl)quinoline) (1). The solid state structure of L1 is described. The catalytic activity of 1 in the transfer hydrogenation of various ketones by 2-propanol at 82 °C, has been studied and compared with the activity of the known catalyst precursors cis -[RuCl2 (PPh3 )2 (L2)] (L2 = 2-(2'-pyridyl)quinoline) (2), cis -[RuCl2 (PPh3 )2 (L3)] (L3 = 2-(2′-pyridyl)quinoxaline) (3) and cis -[RuCl2 (PPh3 )2 (bipy)] (bipy = 2, 2′-bipyridine) (4). The ruthenium monohydride complex [RuHCl(PPh3 )2 (L3)] 3-H (Cl cis to H) was prepared from the reaction of 3 with 2.5 equivalents of a KO i Pr solution. Reaction of 3 with 10 equivalents of KO i Pr yields the cis-[RuH2 (PPh3 )2 (L3)] (3-H2 ). Treatment of 1, 2 and 4 with KO i Pr (in excess) affords the ruthenium cis-dihydride complexes [RuH2 (PPh3 )2 (L1)] (1-H2 ), [RuH2 (PPh3 )2 (L2)] (2-H2 ) and [RuH2 (PPh3 )2 (bipy)] (4-H2 ). The formation of 1-H2, 2-H2, 3-H2 and 4-H2 is supported by NMR spectroscopic data. The cis -dihydrides 1-H2 to 4-H2 catalyze successfully the transfer hydrogenation of benzophenone to benzhydrol in the absence of a base, suggesting that presumably the active catalyst is a ruthenium dihydride complex (RuH2 ). Catalyst 1 has been potentially recovered and reused at least four times.